Maimonidean Criticism and the Maimonidean Controversy, 1180-1240 - Silver, Daniel Jeremy (European History and Culture - Book Archive pre-2000., 1965)
Although Maimonides is now known as one of the greatest Jewish theologians and philosophers of the middle ages, his writings were denounced from the outset - first in the East then in the West. In fact, by the mid-1230's the so-called Maimonidean Controversy that had begun within the Jewish community had spread to encompass much of the Christian scholarly world as well. Daniel Silver's Maimonidean Criticism constitutes a landmark in the historiography of Maimonideanism in general and of the controversy of the 1230s in particular. Brill has thus brought this important book back into print for students wishing an introduction to this debate.